(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background: Reproductive failure is a significant public health concern. Vitamin D influences steroidogenesis and ovarian follicular development. AMH has a crucial role in the regulation of follicular recruitment and oocyte development. Several studies have recently shown that serum AMH is affected by several factors including obesity, serum leptin and serum vitamin D. Results from studies are conflicting with some suggesting that vitamin D status is associated with ovarian reserve, whereas other studies have not found any significant correlation between vitamin D and AMH levels. Objective: To evaluate the association between vitamin D deficiencies with serum anti-mullerian hormone in infertile women. Materials and methods: The study population was the infertile women of 20-34 years of age. The women having serum anti-mullerian hormone levels ≤ 1 ng/ml were grouped as diminished ovarian reserve and those having serum anti-mullerian hormone levels > 1 ng/ml were grouped as normal ovarian reserve. Serum anti-mullerian hormone and serum vitamin D levels were measured at the same day. Result: Vitamin D deficiency was defined when vitamin D levels were ≤ 20ng/ml. All infertile women with normal and diminished ovarian reserve are deficient in vitamin D. The mean serum AMH was 1.42±1.49 in vitamin D level ≤20 ng/ml and 3.14± .45 in vitamin D level >20 ng/ml. Bivariate analysis was done to see that vitamin D deficiency was significantly more (calculated odds ratio 4.40) in those with diminished ovarian reserve. There was significant positive correlation between serum vitamin D level and serum anti-mullerian hormone. Conclusion: Vitamin D deficiency is associated with low serum anti-mullerian hormone in infertile women. J Bangladesh Coll Phys Surg 2024; 42: 19-24